Monocyte depletion enhances neutrophil influx and proneural to mesenchymal transition in glioblastoma - Chen, Zhihong; Soni, Nishant; Pinero, Gonzalo; Giotti, Bruno; Eddins, Devon J.; Lindblad, Katherine E.; Ross, James L.; Puigdelloses Vallcorba, Montserrat; Joshi, Tanvi; Angione, Angelo; Thomason, Wes; Keane, Aislinn; et al. (Nature communications, 2023)
Myeloid cells comprise the majority of immune cells in tumors, contributing to tumor growth and therapeutic resistance. Incomplete understanding of myeloid cells response to tumor driver mutation and therapeutic intervention impedes effective therapeutic design. Here, by leveraging CRISPR/Cas9-based genome editing, we generate a mouse model that is deficient of all monocyte chemoattractant proteins. Using this strain, we effectively abolish monocyte infiltration in genetically engineered murine models of de novo glioblastoma (GBM) and hepatocellular carcinoma (HCC), which show differential enrichment patterns for monocytes and neutrophils. Eliminating monocyte chemoattraction in monocyte enriched PDGFB -driven GBM invokes a compensatory neutrophil influx, while having no effect on Nf1 -silenced GBM model. Single-cell RNA sequencing reveals that intratumoral neutrophils promote proneural-to-mesenchymal transition and increase hypoxia in PDGFB -driven GBM. We further demonstrate neutrophil-derived TNF-a directly drives mesenchymal transition in PDGFB -driven primary GBM cells. Genetic or pharmacological inhibiting neutrophils in HCC or monocyte-deficient PDGFB -driven and Nf1 -silenced GBM models extend the survival of tumor-bearing mice. Our findings demonstrate tumor-type and genotype dependent infiltration and function of monocytes and neutrophils and highlight the importance of targeting them simultaneously for cancer treatments. Myeloid cells are the predominant cell type in the tumor microenvironment of human and murine glioblastoma (GBM). By generating a mouse model deficient for all monocyte chemoattractant proteins, here the authors show that blocking monocyte recruitment promotes a compensatory neutrophil influx and that concomitant neutrophil inhibition is required to improve survival in GBM preclinical models.